2022
DOI: 10.1128/aem.00018-22
|View full text |Cite
|
Sign up to set email alerts
|

Soil Properties and Moisture Synergistically Influence Nontuberculous Mycobacterial Prevalence in Natural Environments of Hawai’i

Abstract: Nontuberculous mycobacteria (NTM) are ubiquitous in the environment, being found commonly in soils and natural bodies of freshwater. However, little is known about the environmental niches of NTM and how they relate to NTM prevalence in homes and other human-dominated areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Previous work has identified iron oxide minerals as a key soil component that supports NTM in Hawai'i (Glickman et al, 2020;Parsons et al, 2022). Our observations that phosphorus, sulfur, and TOC in Kīlauea soil are positively associated with NTM presence highlight additional factors that may enrich for NTM, particularly (a) Phylogenetic relationships between Kīlauea ash-derived M. abscessus (red squares), environmental isolates (triangles), and respiratory isolates (circles) from individuals residing in Hawai'i.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Previous work has identified iron oxide minerals as a key soil component that supports NTM in Hawai'i (Glickman et al, 2020;Parsons et al, 2022). Our observations that phosphorus, sulfur, and TOC in Kīlauea soil are positively associated with NTM presence highlight additional factors that may enrich for NTM, particularly (a) Phylogenetic relationships between Kīlauea ash-derived M. abscessus (red squares), environmental isolates (triangles), and respiratory isolates (circles) from individuals residing in Hawai'i.…”
Section: Discussionmentioning
confidence: 72%
“…Previous work has identified iron oxide minerals as a key soil component that supports NTM in Hawai'i (Glickman et al., 2020 ; Parsons et al., 2022 ). Our observations that phosphorus, sulfur, and TOC in Kīlauea soil are positively associated with NTM presence highlight additional factors that may enrich for NTM, particularly within the state of Hawai'i and other volcanic environments.…”
Section: Discussionmentioning
confidence: 99%
“…Hawai’i has more NTM lung disease cases per capita than any other US state [ 5 ]. Our prior research of 62 households found that clinically important NTM species are prevalent in the Hawai’i environment [ 6 ] and may be the source of the high rate of NTM infections [ 7 , 8 ]. To more broadly study NTM diversity, a Hawai’i-based community science network involving more than 200 local students and teachers from 11 different schools collected more than 2,800 environmental samples from across O’ahu, Kaua’i, Hawai’i Island, and Maui [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the presence of the organism in municipal drinking water sources, hospital water systems, and even industrial cooling towers [2,[47][48][49][50] increases the likelihood of exposure and colonization, even in non-developing nations with appropriately hygienic water supply infrastructure. Moreover, soil and dust-derived exposures can increase the risk of environmentally-sourced infections [51][52][53], as can the organism's fitness towards causing transmission through fomite contact [54], and together, these obstacles make prevention and treatment of MABC infections a formidable challenge. Given these issues, development of novel agents that circumvent MABC resistance mechanisms is an unmet and highly warranted need.…”
Section: Introductionmentioning
confidence: 99%